Exergame com cicloergômetro para a reabilitação de pacientes - Battisti, Douglas (2020)
Computer games are already recognized as a motivational tool in the rehabilitation of patients; when games promote exercise these are called exergames. Traditional rehabilitation includes exercises that are often considered repetitive and boring. For patients who have been in the ICU for a long time, early mobilization with a cycle ergometer has been used, a stationary equipment designed to allow cyclical rotations and promote resistive exercises. This method restores the functional state of the patient who has suffered adverse effects from immobility. This work aims to develop a solution for physiotherapists capable of motivating patients during early mobilization with a cycle ergometer, in addition, we evaluated with physiotherapists, specialized in intensive care, the applicability of the exergame with patients. The development of the exergame includes the adaptation of the cycle ergometer with Arduino, the connection of physiological sensors to the exergame and the customization of the game session to each patient.